Uses of madness: towards the recognition of new interpretations of human suffering - Miguel Salas Soneira (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
This article addresses the controversy associated with the construct schizophrenia/psychosis/madness, indicating the need to acknowledge the multiplicity of experiences and interpretations which arise through the use of the construct. The plurality and complexity intrinsic to the phenomenon, the discrepancies in its possible meanings and the value of first-hand experience are indicated as aspects whose recognition is indispensable to both understanding suffering and confronting it socio-educationally. Using interviews carried out in September 2013 and May 2014 with six people diagnosed at least with schizophrenia, who gave their informed consent to participate, these dimensions are explored. Additionally, madness is examined from a queer perspective as a possible space of political expression that permits new paths and forms of social circulation among those afflicted.